Management Reconstruction of Eyelid Kissing Nevus - Permatasari, Lissa Novia; Doemilah, Ratna (Vision Science and Eye Health Journal, 2024)
Introduction: An unusual type of congenital nevus known as "kissing nevus" develops on one eye's upper and lower lid and becomes enormous while the eyelids are closed. Reconstruction is complex since it creates both aesthetic and functional issues. Case Presentation: A 23-year-old female patient attended our ophthalmology outpatient clinic stating that she had a painless, non-progressing black nevus covering her left upper and lower eyelid since birth. The dark brown-black, 55 mm in size, with hypertrichosis that extended to the cheek and covered about two-thirds of the left upper and lower eyelid edges. A free supraclavicular skin transplant restored the complete nevus shortly after removal. We performed canthoplasty, lateral canthopexy, and full-thickness graft procedures. Three weeks following the procedures, the result was satisfactorily proved. Through histopathological examination, intradermal nevus pigmentosus was identified. Conclusions: A secure, trustworthy, and aesthetically pleasing option for head and neck deformities reconstruction involves a free supraclavicular graft.